(3GSJNOGe GdCdYGH GdGHJcGQjI dJfejI egGQGJ GdJacjQ GdfGbO dWad GdQhVI (B/ s - (3fhGd MeOj YeQ EHQGgje s; (3LjgGf YHO GdaJGM YRGe (B: s; (3SYGO GdSjO EHQGgje (B: s ((3GdbGgQI (B: s (3fhGd MeOj YeQ EHQGgje (B: s, 2014)
(3jgOa GdHMK Edi JfejI egGQGJ GdJacjQ GdfGbO dWad GdQhVI ef NdGd EYOGO HQfGeL CdYGH GHJcGQjI(B: (3hJchfJ YjfI GdOQGSI ef (B(60) (3Wad hWadI ef CWaGd GdeSJhi GdKGfj dQjGV GdCWaGdhGdJj JJQGhM CYeGQge GdRefjI ef (B(6 (3`` (B7 ) (3SfhGJ hbO JbSeJ Ydi GdfMh GdJGdj(B: (3JchfJ GdeLehYI GdJLQjHjI ef (B(30) (3Wad (B( 13 (3PchQ `` (B17 (3EfGK(B): (3hJchfJ GdeLehYI GdVGHWI ef (B(30) (3Wad (B( 14 (3PchQ `` (B16 (3EfGK(B): (3hbO Je GSJNOGe GdefgL THg GdJLQjHj(B: (3hJMOOJ COhGJ GdOQGSI aj GNJHGQ PcGA GdCWaGd GdeUahaGJ GdeJJGHYI GdedhfI (B"(3dQGaf(B" ((3EYOGO(B: (3EHQGgje MeGO (B2002): (3GdebjGS GdeUhQ degGQGJ GdJacjQ GdfGbO dWad GdQhVI (B((3EYOGO GdHGMKI(B): (3HQfGeL GdCdYGH GdGHJcGQjI dJfejI egGQGJ GdJacjQ GdfGbO dWad GdQhVI (B((3EYOGO GdHGMKI(B): (3hbO CSaQJ GdfJGFL HCf GSJNOGe HQfGeL GdCdYGH GdGHJcGQjI cGf dg JCKjQ EjLGHj Ydi JfejI egGQGJ GdJacjQ GdfGbO dWad GdQhVI(B. s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI QjGV GdCWaGd (B- (3bSe GdYdhe GdCSGSjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCdYGH GdGHJcGQjI s; (3GdJacjQ GdfGbO s; (3Wad GdQhVIs